“A Dem Fine Woman”: Female Artists and Actresses' Visual Representations of Beautiful Evil - Allan, Emily (Kansas State University. K-State Libraries, 2017)
The scene is iconic: a faun walking through a snowy wood holding an umbrella over him and his companion, a young girl. This evocative image has become the foremost visual representation of the beloved works of C.S. Lewis, his seven-book Chronicles of Narnia. Having grown up reading the books, beginning with my introduction to the seminal The Lion, the Witch, and the Wardrobe at age eight, I can attest to the powerful influence these books, with their fantastical settings and characters, had on my life. While most readers are enthralled with the wonderfully good lion Aslan or the world found beyond the wardrobe, I was captivated by the titular witch. I spent hours looking at the illustrations of her in my books and shivering when I heard the commanding voice of Elizabeth Counsell’s performance of the White Witch in the Radio Theatre broadcast audiobooks. My obsession has extended well into my adult life as I encounter new depictions of my favorite villain. The incarnation of evil, Queen Jadis the White Witch, has been visually brought to life by three women over the years. Pauline Baynes created the official illustrations for the Narnia novels, Barbara Kellerman portrayed Jadis in the BBC's 1988 TV miniseries, and Tilda Swinton took on the role for the 2005 feature film. The progression of the depictions over the years has illuminated the source of the Witch’s power over other characters and readers alike. Baynes’ original illustrations set the standard, while the following film adaptations either fail to meet the standard, in the case of Kellerman’s melodramatic portrayal that undermines the character, or supersede the standard in the way that Swinton seamlessly reimagines the villainess to fit the 21st century.
Citation: Allan, E. (2017) “A Dem Fine Woman”: Female Artists and Actresses’ Visual Representations of Beautiful Evil. Unpublished manuscript, Kansas State University, Manhattan, KS.
Kirmser Undergraduate Research Award - Individual Non-Freshman Category, honorable mention